WAROK DALAM SEJARAH KESENIAN REOG PONOROGO (Perspektif Eksistensialisme) - Kencanasari, Lisa Sulistyaning (Jurnal Filsafat "WISDOM", 2009)
AbstractWarok as one of Reog Ponorogo performance elements contains a philosophical value. In the history of reog, the figure of Warok is a leader personality who is willing to sacrifice himself for the sake of public needs rather than himself or his group. The struggling value that is a role model for national youth relates to morality. Warok assumed that policies of the king which is influenced by his wife (the queen) harm public needs so that the problem must be overcome soon.The emphasize of this research is the value of bravery and willing to struggle for public needs which is deeply rooted inWarok’s soul regarding the unity and welfare of their kingdom.Stand for the truth and public needs is one of the principals of Warok in guarding the unity of their kingdom although they have to fight against their own king. Warok use the reog performance as a cynicism aimed to the king. They never doubt their decision and action so that it could be a guidance for national morality concept of Indonesia.Keyword: Warok, Warok’s existence, Reog Ponorogo.